The Role of Madrasah Principal in Addressing Bullying Issues - Ayu Azhari; Inom Nasution (EDUTEC : Journal of Education And Technology, 2024)
Cases of bullying can occur at all levels of education from elementary to tertiary level. Bullying can cause mental damage to a person with severe social and psychological consequences, therefore especially madrasa heads as leaders in educational institutions and teachers and school staff must pay full attention to the problem of bullying. This research aims to determine the role of the madrasa head as the leader of an educational organization in overcoming the problem of bullying in marsah. This research was conducted at Mas Al Wasliyah 22 Tembung using a qualitative phenomenological research method. There were three participants who were selected and willing to become participants in this research, namely the head of the madrasa, the deputy head of the madrasa for student affairs, and one of the Bk teachers. Data collection carried out in this research was interviews by recording audio with a cellphone, recording information provided by participants using writing tools and in the form of photo documentation during the interview. The form of bullying that occurs at Mas Al Wasliyah 22 Tembung is a form of verbal bullying, where verbal bullying is harsh or cruel words, insults or hate speech. Bullying that often occurs is between women. Overcoming the problem of bullying at Mas Al Wasliyah 22 Tembung is by bringing together the perpetrator and the victim and providing sanctions so that the bullying problem does not happen again. The role of the madrasa head in overcoming the problem of bullying at Mas Al Wasliyah 22 Tembung is providing outreach, training for teachers and staff or meetings between teachers and staff, anti-bullying policies, supervision and monitoring, responding to reports relating to student problems such as bullying, building a climate positive school, encouraging student participation, and communicating with students' parents and seeing the plans they have made and discussing, measures of effectiveness that have been implemented.